Mobile development with Adobe Flash Professional CS5.5 and Flash Builder 4.5 : learn by video (Peachpit Press, 2011)
"Designers and developers can now use their Adobe Flash Professional, Flex, and ActionScript skills to quickly begin developing applications for the iPhone, iPad, and iPod touch, as well as for Android devices. In this in-depth course, you'll learn from the ground up how to set up your system to become a mobile developer, create applications, and master each step of the publishing process (including how to get a working Apple certificate to place your app in the App Store). Coverage also includes features in new CS5.5 such as improved Text Layout Framework functionality and code snippets that let you easily take advantage of mobile features such as the accelerometer. You'll also learn best-practices for working smart, as well as what kinds of applications and utilities are most appropriate for Flash-platform development."--Resource description page.